2008
DOI: 10.1111/j.1443-1661.2008.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Hemostasis With Metallic Hemoclips for Iatrogenic Mallory‐weiss Tear Caused by Endoscopic Examination

Abstract: Application of hemoclips was effective for bleeding MWT during endoscopic procedures, which warranted prophylactic application of hemoclips on MWT during endoscopic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“…The eradication of H. pylori is known to reduce the recurrence of peptic ulcers [4,5] and rehemorrhage [6]. However, upper gastrointestinal bleeding is still one of the most common and serious clinical complications of peptic ulcers [7][8][9][10][11][12][13]. In the past 25 years, various endoscopic hemostatic methods for bleeding ulcers have been developed, and endoscopic hemostasis is the first-choice treatment for upper gastrointestinal bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…The eradication of H. pylori is known to reduce the recurrence of peptic ulcers [4,5] and rehemorrhage [6]. However, upper gastrointestinal bleeding is still one of the most common and serious clinical complications of peptic ulcers [7][8][9][10][11][12][13]. In the past 25 years, various endoscopic hemostatic methods for bleeding ulcers have been developed, and endoscopic hemostasis is the first-choice treatment for upper gastrointestinal bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that MWTs may occur iatrogenically during EGD (5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and during endoscopic submucosal dissection (ESD) (15). Although iatrogenic MWTs are generally caused by retching or forceful vomiting during an EGD or ESD procedure (5,11,15), in some cases, no retching or struggling was found to contribute to the development of MWT (6), as in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several additional therapeutic procedures may be applied for the treatment of a bleeding MWT, such as endoscopic hemoclipping, endoscopic band ligation, and endoscopic injection therapy (8,9,15,19). Penson et al emphasized the need to admit patients with iatrogenic MWTs (as in our patient) for 24 hours observation (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a massive clot is covering the ulcer base preventing the visualization of the responsible vessel, the clot is removed using an irrigation system. Hemoclipping is performed continuously until hemostasis has been confirmed [23,25]. As to the use of absolute ethanol, it is directly injected in aliquots of 0.1-0.2 mL into areas around the bleeding vessels using an endoscopic local injection needle to a total volume of 1 mL [23,24].…”
Section: Methodsmentioning
confidence: 99%